Measurement of asymmetrical homogeneous object by using chain code algorithm and virtual center of gravity - Kurniawan, Wawan; Nehru (Journal of physics. Conference series, 2019)
Current methods of measurement of asymmetrical homogenous objects still largely involve various kinds of experimental analysis that are complicated and time-consuming. One of the experiments to measure an object's center of mass is carried out by hanging the object by using pieces of rope in different positions. The point where the rope meet is taken as the object's center of mass and weight. This research is purposed to develop a system to measure area, center of mass, and center of weight of an asymmetrically-shaped object by using digital image processing. The process is initiated by doing a pre-processing method that is purposed to increase the image quality. Then, a method of feature extraction of edge detection and chain code algorithm are used to measure the peripheral size and area of each side of the object. The result and analysis of the area are used to determine the object's center of mass and weight. This digital application will determine the virtual center of mass and center of gravity that are needed to measure an asymmetrically-shaped object in a real-time mode. This application can also be used to measure an object indirectly if the object is not present physically.